A new species of the genus Calambus C.G. Thomson, 1859 (Coleoptera: Elateridae: Dendrometrinae) from China, with notes on the other species of the genus of the East Palaearctic region - Prosvirov, Alexander S. (Zootaxa, 2018)
The species of the genus Calambus C.G. Thomson, 1859 of the East Palaearctic region are discussed. Calambus angulatus sp. nov. is described from Yunnan province of China. C. kusuii Ôhira, 1994 is recorded for the first time from Russia (Sakhalin and Kuril Islands), notes on the morphology of this little-known species are given. A key to the known species of the Calambus of the Palaearctic region is provided. A total of 8 species of the genus have been recorded in the region to date.